Rural livelihoods at Dwesa/Cwebe: poverty, development and natural resource use on the Wild Coast, South Africa - Timmermans, Herman Gerald (Rhodes University, Faculty of Science, Department of Environmental Science, 2004)
This thesis uses the sustainable rural livelihoods framework to investigate the livelihoods of communities residing adjacent to a remote protected area on the Wild Coast. The communities living in the area are among the poorest in South Africa and are largely dependent on migrant remittances and state welfare grants for their survival. Soon after South Africa's first democratic elections in 1994, the communities lodged a land claim against the protected area on the basis of past removals. In 2001, their land rights to the protected area were restored, opening up new avenues for the development of the area. It is argued that livelihood systems in the area are complex, varied and dynamic, and that for development to be sustainable, it needs to be informed by a thorough understanding of the many factors that shape the context in which livelihoods are generated. The research is based primarily on 'in-depth' micro-studies of two villages in the area - Ntubeni and Cwebe. It includes a detailed assessment of the extent and distribution of poverty and the various factors that make households vulnerable to livelihood shocks. The role of the rich and diverse natural resource base, the property rights associated with it, and the under-development of infrastructure and services in the area, are discussed in relation to livelihood prospects. A systems approach is used to examine the various ways in which livestock husbandry, cropping, natural resource use, employment and welfare dependence interact. Finally, the thesis examines in some detail the distribution of household assets, livelihood strategies and livelihood outcomes between the two villages, and between households in different income groups.
Keywords: Poverty -- South Africa -- Eastern Cape; Rural poor -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Land reform -- South Africa -- Eastern Cape; Sustainable development -- South Africa -- Eastern Cape -- Citizen participation; Conservation of natural resources -- South Africa -- Eastern Cape; Income distribution -- South Africa -- Eastern Cape; Household surveys -- South Africa -- Eastern Cape